Legal Strategies in Empowering Msmes Through Assistance to Support The Local Economic Ecosystem in Banyuanyar Village - Itok Dwi Kurniawan; Dara Pustika Sukma; Ismawati Septiningsih; Bambang Santoso; Muhammad Rustamaji; Jose Gama Santos (Universitas Negeri Semarang, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are a vital pillar of the national economy due to their contribution to job creation and local economic resilience. However, in rural areas such as Banyuanyar Village, MSMEs still face serious challenges, particularly in terms of business legality. Limited understanding of the importance of business licensing, restricted access to information, and financial constraints remain the main obstacles for MSME actors to obtain proper legal status. In response to these challenges, an assistance program was implemented with the aim of optimizing the legality of MSME products through three main approaches: education, technical assistance, and financial facilitation. The activities were carried out using interactive lectures, Focus Group Discussions (FGD), and participatory approaches (Built-in Participatory). The results of the FGD revealed that Banyuanyar Village already has an economic potential based on the concept of